FACTORS RELATED TO THE WORK SATISFACTION OF EMPLOYEES IN THE HOSPITAL MOTHER AND CHILD DHIA CIPUTAT TAHUN 2018 - Triani Kholilatun Romsi; Mustakim Mustakim (The Indonesian Journal of Public Health, 2020)
Job satisfaction is one of the important factors to be considered by the organization. The satisfaction felt by employees in their work will minimize the high number of turnover and absenteeism of employees and can increase productivity and employee loyalty to the organization. Research method is an analytical study with a quantitative approach and a cross sectional study design. Data collection is done by questionnaire. The population in this study is all employees who worked in the Hospital of Mother and Child X Ciputat. Sample in this study were 50 respondents. Data analysis was performed using univariate and bivariate. The results of the study showed that employees who felt dissatisfied worked at the Hospital of Mother and Child X Ciputat by 36.0%. The results also show that there are four variables that have a significant relationship with employee’s job satisfaction at the X Ciputat Mother and Child Hospital including salary, organizational policy, job security, and working conditions. Therefore the hospital is advised to conduct employee performance surveys periodically and continuously to evaluate employee performanceKey Words : Job satisfaction, employee, hospital